The Primacy of Microclimate and Thermal Comfort in a Walkability Study in the Tropics: A Review - Arif, Victorina; Yola, Lin (Journal of Strategic and Global Studies, 2020)
One of the urgent environmental issues that are encountered by densely populated cities today is climate change and Urban Heat Island (UHI) which are increasing significantly. In the development of outdoor spaces or urban public spaces, there are environmental issues that affect the comfort of human activities. Meteorological, physiological, and psychological parameters affect the thermal comfort of humans doing their activities outdoors. Walking as one of the outdoor activities, in terms of urban design, there is not much mention of climate factors in identifying the success of outdoor space design. Walkability, the comfort level of walking is one of the parameters that many researchers discuss in the context of activity studies related to outdoor activities. This study aims to further review the development of literature relating to the urban microclimate, thermal comfort to walkability, especially in high-density tropical cities.